Characterisation of particles in solution – a perspective on light scattering and comparative technologies. Issue 1 (31st December 2018) - Maguire, Ciarán Manus; Rösslein, Matthias; Wick, Peter; Prina-Mello, Adriele
ABSTRACT: We present here a perspective detailing the current state-of-the-art technologies for the characterisation of nanoparticles (NPs) in liquid suspension. We detail the technologies involved and assess their applications in the determination of NP size and concentration. We also investigate the parameters that can influence the results and put forward a cause and effect analysis of the principle factors influencing the measurement of NP size and concentration by NP tracking analysis and dynamic light scattering, to identify areas where uncertainties in the measurement can arise. Also included are technologies capable of characterising NPs in solution, whose measurements are not based on light scattering. It is hoped that the manuscript, with its detailed description of the methodologies involved, will assist scientists in selecting the appropriate technology for characterising their materials and enabling them to comply with regulatory agencies' demands for accurate and reliable NP size and concentration data. Graphical Abstract: